Cybersecurity with Quantum Cryptography: An Analysis of Current Techniques and Future Trends - Omol, Edwin; Kibuku, Rachael; Abuonji, Paul (International Journal of Science, Technology & Management, 2025)
Using a systematic literature review methodology comprising the following stages: Identification of Relevant Literature, Screening and Selection, Data Extraction and Synthesis, Qualitative Analysis, and SWOT Analysis, this paper explores the role of quantum cryptography in enhancing cybersecurity. The analysis begins with an introduction to the vulnerabilities of classical cryptography in the context of quantum computing advancements. It delves into Quantum Key Distribution (QKD) protocols such as BB84 and E91, Quantum Random Number Generators (QRNGs), and post-quantum cryptography algorithms in detail. Real-world case studies are presented to illustrate the practical applications and advancements in quantum cryptographic techniques. Additionally, the paper addresses the challenges associated with implementing quantum cryptography and proposes strategies for its integration with existing cybersecurity frameworks. The discussion on future trends highlights anticipated technological advancements, potential applications in quantum internet and blockchain security, suggested research directions, and policy implications. The significance of quantum cryptography in securing sensitive data and establishing trust in critical sectors is thoroughly emphasized.